Quality of Local Rams Meat Given Fermented Cassava Peel-Based Feed Using Local Microorganisms - Dirja (Talenta Publisher, 2020)
This research aims to examine the provision of fermented cassava peel using local microorganisms on the quality of local male lamb meat. This research was conducted at Mr. Praditya Rahardja farm, Jalan Bunga Rinte, Kecamatan Medan Tuntungan, Kota Medan, the Food Technology Laboratory of the Faculty of Agriculture and the Laboratory of Biochemistry/Chemistry Faculty of Mathematics and Natural Sciences, University of North Sumatra, using 12 local male sheep from December 2019 to march 2020. This research designed using a completely randomized design (CRD) with 4 treatments and 5 replications. The treatment is various levels of fermented cassava peel using local microorganisms consisted of P0: ration without the addition of fermented cassava peel using local microorganisms; P1: ration with the addition of 25% fermented cassava peel using local microorganisms; P2: ration with the addition of 50% fermented cassava peel using local microorganisms and P3: ration with the addition of 75% fermented cassava peel using local microorganism. This research parameters are meat water content, meat protein content, meat fat content and meat shrinkage.The results showed that the level of concentrate gave a very significant difference (P <0,01) of protein content and meat fat content, but did not provide a significant difference (P> 0,05) of water content and cooking meat shrinkage. The conclusion of this research is the provision of fermented cassava peel using local microorganisms has a very significant influence on the lamb meat quality of male local sheep